Pentingnya Pendidikan Kewarganegaraan untuk Mewujudkan Peserta Didik yang Cerdas dan Baik (Smart and Good Citizen) - Acep Iyan; Dinie Anggraeni Dewi (Civiliza Publishing, 2021)
Citizenship education has an important role in shaping character and acts as a citizen's self-actualization, both individually and in groups according to their respective rights and obligations. In building the nation's character into a strong character, character education is needed, The existence of a nation is seen from the character of its citizens, the character of a strong citizen becomes a nation with dignity and of course respected by other nations. Therefore we need a character development process through character learning civic education, in order to create students who excel in all areas of life and become good leaders in the future.